Analisis Pengembangan Agrowisata Kopi Luwak Alas Harum Bali di Desa Tegallalang - DEWI, COKORDA ISTRI TRISNAINA; SURYAWARDANI, I. G. A OKA; WIDHIANTINI, WIDHIANTINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Analysis of the Development of Alas Harum Bali Civet Coffee Agrotourism in Tegallalang Village Alas Harum Bali is one of many agro-tourism in Bali, the location is very strategic in Tegallalang Village. Due the COVID-19 pandemic, the visitors of Alas Harum Bali getting reduce. This research aims to identifying the external and internal factors which gave an impact to the potential of agro-tourism and determined the main strategy and also the alternative strategy to developing the Alas Harum Bali Agro-Tourism. This research was conducted using the IE Matrix Analysis method to formulate general business development strategies and SWOT Matrix Analysis to formulate alternative business development strategies for Alas Harum Bali. The right marketing strategy applies SO, WO, ST and WT which can be implemented in Alas Harum Bali agro-tourism, among others, are as follows. The SO (strengths-opportunities) strategy is to pay attention to the facilities and attractions that are owned as well as human resources so that they are able to provide optimal services. The ST strategy (strengths-threats) is to pay attention to the facilities owned and develop them so that they are able to overcome unfavorable natural conditions. The WO (weaknesses-opportunities) strategy is to pay attention to facilities and improve the facilities and infrastructure provided so that they are in accordance with the prices offered to visitors.